2023
DOI: 10.3390/f14061101
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Trivalvaria costata Chloroplast Genome and Molecular Evolution of rps12 Gene in Magnoliids

Abstract: Chloroplasts (cp) are important organelles in plant cells that have been widely used in phylogenetic, molecular evolution, and gene expression studies due to their conserved molecular structure. In this study, we obtained the complete cp genome of Trivalvaria costata (Annonaceae) and analyzed its structural characteristics. Additionally, we analyzed the rps12 gene in the phylogenetic framework of magnoliids. The T. costata cp genome comprises 1,662,002 bp and contains 132 genes. We detected 48 simple sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Our results support Annonoideae and Malmeoideae as monophyletic groups and sister clades, with Cananga odorata outside of them, followed by Anaxagorea javanica. Additionally, we observed that the phylogenetic relationships within Malmeoideae species had low support in all trees except the BI tree, consistent with previous research (Ping et al, 2023). Furthermore, we found that Chieniodendron hainanense is located within Malmeoideae, which is consistent with the findings of Thomas et al (2012), who placed Chieniodendron within Meiogyne (Malmeoideae).…”
Section: Phylogenetic Relationship Of Annonaceaesupporting
confidence: 92%
See 3 more Smart Citations
“…Our results support Annonoideae and Malmeoideae as monophyletic groups and sister clades, with Cananga odorata outside of them, followed by Anaxagorea javanica. Additionally, we observed that the phylogenetic relationships within Malmeoideae species had low support in all trees except the BI tree, consistent with previous research (Ping et al, 2023). Furthermore, we found that Chieniodendron hainanense is located within Malmeoideae, which is consistent with the findings of Thomas et al (2012), who placed Chieniodendron within Meiogyne (Malmeoideae).…”
Section: Phylogenetic Relationship Of Annonaceaesupporting
confidence: 92%
“…In Annonoideae, 10 to 32 protein-coding genes enter the IR region in Annonoideae, which directly increases the total number of genes. Notably, in Annona, 5'-rps12 is located in the IR region, which is rarely reported before (Ping et al, 2023). In ferns and gymnosperms, it has been found that 3'-rps12 enters or leaves the IR region as the IR region expands or contracts, and it has been shown that 3'-rps12 in the IR region has reduced substitution rates and a more conserved sequence signature (Ping et al, 2021b, c).…”
Section: Structural Rearrangements Of Plastomes In Annonaceaementioning
confidence: 94%
See 2 more Smart Citations